53 Associations of four nurse staffing practices with hospital mortality: key lessons for hospital managers and leaders. (16th November 2020) - Rochefort, Christian M; Beauchamp, Marie-Ève; Audet, Li-Anne; Abrahamowicz, Michal; Bourgault, Patricia
Abstract : Background: Cross-sectional studies of hospital-level administrative data have suggested that four nurse staffing practices – using adequate staffing levels, higher proportions of Registered Nurses (RNs) (skill mix), and more educated and experienced RNs – are each associated with reduced hospital mortality. To increase the validity of this evidence, patient-level longitudinal studies assessing the simultaneous associations of these staffing practices with mortality are required. Methods: A dynamic cohort of 146, 349 adult medical, surgical, and intensive care patients admitted to a Canadian university health center was followed for seven years (2010–2017). We used a multivariable Cox proportional hazards model to estimate the associations between patients' time-varying cumulative exposure to measures of RN understaffing, skill mix, education and experience, each relative to nursing unit and shift means, and the hazard of in-hospital mortality, while adjusting for patient and nursing unit characteristics, and modeling the current nursing unit of hospitalization as a random effect. Results: Overall, 4, 854 in-hospital deaths occurred during 3, 478, 603 patient-shifts of follow-up (13.95 deaths/10, 000 patient-shifts). In multivariable analyses, every 5% increase in the cumulative proportion of understaffed shifts was associated with a 1.0% increase in mortality (HR: 1.010; 95%CI: 1.002–1.017; p = 0.009). Moreover, every 5% increase in the cumulative proportion of worked hours by baccalaureate-prepared RNs was associated with a 2.0% reduction of mortality (HR: 0.980; 95%CI: 0.965–0.995, p = 0.008). RN experience and skill mix were not significantly associated with mortality. Conclusions: Reducing the frequency of understaffed shifts and increasing the proportion of baccalaureate-prepared RNs are associated with reduced hospital mortality.